1951
DOI: 10.1111/j.1151-2916.1951.tb13491.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Compositions Having Negative Linear Thermal Expansion

Abstract: Compositions having negative linear thermal expansions ranging from 0 to -0.38~0 have been obtained in two areas of the system lithia-alumina-silica.Petrographic and X-ray examinations indicate the presence of three principal crystalline phases, each of which is a solid solution: 0-eucryptite, 0-spodumene, and a n unidentified quartzlike phase. All compositions were prepared from lithium carbonate, clay, flint, a n d alumina. Some compositions have been prepared which, for all piactical purposes, exhibit no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1
1

Year Published

1964
1964
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 2 publications
1
16
1
1
Order By: Relevance
“…The ability of this sintering technique to obtain dense ceramics will be demonstrated. Previous studies have shown that even for pressureless sintering methods it is necessary to control the sinterability of these ceramics [7] and the variations of thermal expansion coefficient with the LAS composition [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of this sintering technique to obtain dense ceramics will be demonstrated. Previous studies have shown that even for pressureless sintering methods it is necessary to control the sinterability of these ceramics [7] and the variations of thermal expansion coefficient with the LAS composition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intensive effort has been directed at producing ceramics which contain ␤-eucryptite and ␤-spodumene with relatively high content of Li 2 O. [8][9][10] ␤-Eucryptite and ␤-spodumene containing porcelains, with 8.03-11.86 wt.% Li 2 O, have been produced using kaolin, quartz and Li 2 CO 3 as raw materials via conventional ceramic a Rock A and rock B: Li-bearing pegmatites A and B, respectively. These Li-rich aplite-pegmatite dykes, kindly offered by the Centre of Geology of the University of Porto, were obtained from a deposit (Covas de Barroso district, northern Portugal), whose Li 2 O-content varies between 0.9 and 3.0 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…Following on from this initial observation, the phase equilibria within the LAS system was subsequently investigated in great detail by Roy and co-workers (Roy and Osborne, 1949;Roy et al, 1950), and from this ternary phase diagram, two regions of negative linear thermal expansivity were identified by Smoke (1951) and Hummel (1951). The first is a localized solid solution centred at a composition corresponding to β-eucryptite (LiAlSiO 4 ; composition 1:1:2), the other, a more extended compositional range β-spodumene solid solution, extends from silica-deficient spodumene, to silica-rich petalite (LiAlSi 4 O 10 ; ideal composition 1:1:8).…”
Section: Introductionmentioning
confidence: 99%